Indentifikasi Pemborosan pada Pekerjaan Konstruksi - Amalia Effendy; Meliyana Meliyana; Muhammad Ridha; Tety Sriana; Irwan Syah (Jurnal Teknik Sipil Unaya, 2022)
The rapid development of the Construction Industry is certainly followed by various impacts. These impacts include waste came from the construction industry. Construction contribute to one third of the world's total waste. This research was conducted to identify the materials that most often cause waste in construction work. Data was collected by distributing questionnaires to construction companies, by looking at the characteristics and types of materials that were most frequently wasted. The results showed that the characteristics of construction companies are M1 subqualification (intermediate 1) with working experience more than 10 years. The material that most often wastefully  is cement with a value of 16%.